Synthesis, characterization, x-ray diffraction studies and biological activities of iron(III) and cobalt(II) complexes with alanine - Musa, Shuaibu; O. Idris, S; D. Onu, A (International Journal of Advanced Chemistry, 2018)
The resulted complexes produced between Fe (III) and Co (II) with biological molecules like amino acids play an important role in human life. They can be used as bioactive compounds as well as in industries. Fe (III) and Co (II) complexes are synthesized with Alanine amino acid. The complexes were characterized by X-ray diffraction, magnetic suscetivility, elemental analysis (AAS), molar conductance, melting point, infrared and uv-visible spectrophotometry analyses. The elemental analyses were used to determine the chelation ratio, 1:3(metal: ligands) for iron (III) Alanine and 1:2 ratio for cobalt (II) Alanine. The molar conductivity of the complexes show that the complexes are not electrolytic in nature. The x-ray data suggest monoclinic crystal system for all the complexes with the exception of Co-alanine, which is hexagonal. The magnetic susceptivility and electronic spectra suggest the complexes are high spin with octahedral geometry.The complexes show enhance activity in comparable to the amino acid.Â Â